2016
DOI: 10.1002/2015jb012646
|View full text |Cite
|
Sign up to set email alerts
|

Static Coulomb stress load on a three‐dimensional rate‐and‐state fault: Possible explanation of the anomalous delay of the 2004 Parkfield earthquake

Abstract: We perform quasi‐dynamic modeling of earthquake cycle using laboratory derived rate‐and‐state laws of friction on a homogeneous three‐dimensional fault model. We study effects of the static Coulomb stress loading on clock advance and clock delay of the subsequent event. We carefully investigate dependences of the clock advance on the onset time of the stress load, its amplitude, areal extent, and place of application of the load. We find that these dependences are complex, being controlled by the actual ongoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…Their model reproduced an earthquake sequence of irregular M w 6.0 mainshocks with varying propagation directions. Kostka and Gallovič (2016) modified the dynamic model of Barbot et al (2012) and showed that a stress perturbation, possibly caused by the nearby 1983 Coalinga-Nuñez earthquakes, may have delayed the occurrence of the 2004 Parkfield mainshock.…”
Section: Results From Previous Dynamic Modelingmentioning
confidence: 99%
“…Their model reproduced an earthquake sequence of irregular M w 6.0 mainshocks with varying propagation directions. Kostka and Gallovič (2016) modified the dynamic model of Barbot et al (2012) and showed that a stress perturbation, possibly caused by the nearby 1983 Coalinga-Nuñez earthquakes, may have delayed the occurrence of the 2004 Parkfield mainshock.…”
Section: Results From Previous Dynamic Modelingmentioning
confidence: 99%